Marcella Althaus-Reid’s Marxian Critique of Theology - Waldron, Stephen (Political theology, 2022)
Marcella Althaus-Reid offers a Marxian critique of the production of theology. This article offers analysis of three aspects of this critique: First, it describes how Althaus-Reid diagnoses the intertwined realities of capitalist economies, heterosexual patriarchy in societies, and hierarchical theologies. Second, it traces her use of ideology critique as she adapted Marx’s critique of the Young Hegelians as part of her own critique of Liberation Theologians. Third, it explains her account of the production, marketing, and consumption of theology in relation to her uses of economic metaphors derived from Marx. By isolating the Marxian influence on Althaus-Reid, the article develops an account of her critique as an undressing of theological method that echoes Marx’s critiques of political economy as an unveiling of hidden mechanisms that can be applied more broadly as well. Her critique is then related to how theology can be practiced in more self-aware ways.